The relation between original text and its translation: foreignization of V. Nabokov and domestication of M. Tsvetaeva - Luarsabishvili, Vladimer (Eslavística Complutense, 2015)
The translation was a sphere of interest of professionals, writers and non-professionals during many centuries. From that times the debates about methods of translation originate, including point of views of Cicero, Horace, in time of Bayt al-hikma and St. Jerome, continued in XX century, works of L. Venuti, philosophical theories and audiovisual translation. The goal of our article is to establish the relation between original and translated texts. As an example of the investigation the translations performed by V. Nabokov and M. Tsvetaeva are taken. We analyze the evolution of translational doctrine of V. Nabokov and evaluate the possible reasons which influenced on M. Tsvetaeva to produce the domesticated translation.
Keywords: domestication; foreignization; Nabokov; Tsvetaeva; Lorca.